(untitled) (Marketing Journal, 2026)
Abstract The article examines the main problems and constraints in the development of transport service management under modern conditions. It is shown that the current management system faces infrastructural, financial, institutional, and digital barriers that reduce the overall efficiency of the transport sector. A high concentration of transport activity in the road segment is identified, increasing the load on the road network and raising operational costs. Despite sectoral growth and improvements in logistics performance indicators, investment deficits, safety issues, and environmental risks persist. The necessity of comprehensive modernization of organizational and economic management mechanisms based on strategic planning, digital integration, and sustainable development principles is substantiated. Keywords: transport management, transport services, infrastructure constraints, digitalization, logistics, transport safety, sustainable development.